Editorial: Drug Abuse (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Drug abuse is usually associated with anti-social behaviour. One of the earliest recorded incidence is when the biblical Noah drank too much wine and subsequently exposed his nakedness to his sons, Shem and Japheth (Genesis 9:20-23). Repeated drug abuse has adverse effects on the process of learning, reasoning and solving problems. It lowers ones self esteem while giving the user a false sense of well being.